2017
DOI: 10.1038/pr.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline inhibits TLR- and inflammasome-mediated in vitro inflammatory cytokine production in human blood with greater efficacy and potency in newborns

Abstract: PTX is a potent and efficacious inhibitor of TLR-mediated inflammatory cytokines in newborn cord blood and a promising neonatal anti-inflammatory agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
46
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 38 publications
2
46
0
Order By: Relevance
“…If D = 1: (HBV + BCG) act additively, if D > 1: (HBV + BCG) act antagonistically, and if D < 1: (HBV + BCG) act synergistically. Our laboratory has employed this interaction analysis method in other recently published studies ( 13 , 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…If D = 1: (HBV + BCG) act additively, if D > 1: (HBV + BCG) act antagonistically, and if D < 1: (HBV + BCG) act synergistically. Our laboratory has employed this interaction analysis method in other recently published studies ( 13 , 38 , 39 ).…”
Section: Methodsmentioning
confidence: 99%
“…In previous neonatal pilot studies, PTX improved endothelial cell function, reduced coagulopathy in sepsis and NEC and diminished intestinal permeability by reducing myeloperoxidase activity and oxygen free radical generation [4]. PTX also significantly reduces inflammatory host responses to various stimuli in neonatal blood in vitro and in vivo [5][6][7]. A recent Cochrane review concluded that PTX increases survival and shortens length of hospital stay in neonates with sepsis, and recommended appropriately powered clinical trials be undertaken to confirm these findings [8].…”
Section: Introductionmentioning
confidence: 96%
“…Placental cord blood was collected from healthy term newborns between 38 to 41 weeks gestation who delivered by Cesarean section without labor and without current infection, including documented intrauterine infection (i.e. absence of clinical chorioamnionitis, prolonged fetal membrane rupture over 12h, clinical or laboratory signs of early-onset sepsis, or culture-proven sepsis of the mother or the newborn) or HIV [ 20 ]. Peripheral venous blood was donated with consent from healthy adult donors between 18 to 55 years of age.…”
Section: Methodsmentioning
confidence: 99%
“…We hypothesized that PTX + DEX or AZI (DEX/AZI) may provide broader, more profound and/or synergistic blunting of neonatal Toll-like receptor (TLR)- and/or inflammasome-mediated inflammatory cytokine production. As a model for infection-induced neonatal inflammation, we stimulated blood with TLR agonists (TLRAs) that activate TLR4 (the endotoxin lipopolysaccharide (LPS)), TLR7/8 (R848, an imidazoquinoline that induces adult-level inflammatory cytokine production in newborn monocytes) [ 19 ], or both TLR pathways and the inflammasome including R848 [ 19 ] and the combination of LPS and adenosine triphosphate (ATP) [ 20 ]. Using these whole blood assays, which preserve the age-specific immunomodulatory soluble and cellular factors naturally present in the newborn [ 21 23 ], we compared the anti-inflammatory effects of (PTX+DEX/AZI).…”
Section: Introductionmentioning
confidence: 99%